Satellite-based Applications on Climate Change - Qu, John.; Powell, Alfred; Sivakumar, M.V.K.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
Climate and other environmental changes are drawing unprecedented concern and attention from national governments, international organizations and local communities. Global warming has left noticeable impacts on the environment and the ecosystems it supports (including humans), and has important implications for sustainable economic and social development in the future. Satellite observations of climate and environmental change have become an increasingly important tool in recent years in helping to shape the response of international communities to this critical global challenge. The book presents the latest advances in satellite-based remote sensing of the Earth$1 (Bs environment - ranging from applications in climate and atmospheric science to hydrology, oceanography, hydrology, geomorphology, ecology and fire studies. Introductory chapters also cover key technical aspects such as instrumentation, calibration, data analysis, and GIS tools for decision-making.s
From the Contents: Introduction to Satellite Remote Sensing of Climate -- Overview of Satellite-based Measurements and Applications -- Calibrating A System of Satellites -- MODIS Ten Year Performance to Support Climate Change Study -- Introduction to NOAA Climate Data Record Program -- Comparison of Trends and Solar Forcing in MSU, ERA-40 and NCEP/NCAR Analysis of Stratospheric and Tropospheric Temperature in the period of 1979-2002 -- Development of the Global Mutispectral Imager Thermal Emissive FCDRs -- Atmospheric and climate applications -- Global Precipitation Monitoring -- Developing a Historical Precipitation Record -- Atmospheric Temperature Climate Data Records from Satellite Microwave Sounders.
Keywords: Geography; Earth Sciences; Earth System Sciences; Atmospheric Sciences; Environmental Monitoring/Analysis.; Atmospheric Sciences